Analysis of Physical Fitness Levels Based on the Indonesian Physical Fitness Test (TKJI) Among Sixth-Grade Students of SD Negeri Biringkaloro - Muhammad Amar Ma’ruf Sahba; Jhohan Bastian; Inrawati; Miftahul Janna (CV Lentera Cendekia Indonesia, 2025)
This study aims to analyze the physical fitness levels of sixth-grade students at SD Negeri Biringkaloro based on the Indonesian Physical Fitness Test (TKJI). Using a descriptive quantitative approach, the research assessed 21 students through five test components: 40-meter sprint, pull-up, 30-second sit-up, vertical jump, and 600-meter run. Data were collected using standardized TKJI procedures for the 10–12 age group and analyzed using descriptive statistics. The results indicate that the majority of students fall into the “Poor” and “Very Poor” categories, with 52% categorized as Very Poor and only 5% achieving a Good level. The weakest components were cardiovascular endurance (600-meter run) and upper-body strength (pull-up). These findings suggest that students’ physical fitness levels are still below the expected standards and highlight the need for improved physical activity engagement through more varied PE learning strategies, structured training programs, and increased motivation both in and outside of school. Overall, the study underscores the importance of implementing targeted interventions to enhance students’ physical fitness.